Evolution of monkeypox virus from 2017 to 2022: In the light of point mutations - Desingu, Perumal Arumugam; Rubeni, T. P.; Sundaresan, Nagalingam R. (Frontiers in Microbiology, 2022)
Monkeypox virus (MPXV) causing multi-country outbreak-2022 is related to viruses caused outbreak-2017-18 in West Africa. Still not fully understood which proteins of the MPXV discovered in Nigeria in 2017 have mutated to the extent that it could cause a multi-country outbreak in 2022. Here we report that this monkeypox virus acquires point mutations in multiple proteins in each period, and these point mutations accumulate and become a virus that can root outbreak-2022. Viruses exported from Nigeria to Singapore, Israel, and the UK in 2018-19 were developed as evolutionary ancestors to B.1 viruses (MPXVs causing multi-country outbreak-2022) through MPXV/USA/2021/MD virus. Although these exported viruses have different amino acid mutations in different proteins, mutations in ten proteins are common among them. The MPXV-UK-P2 virus evolved with only mutations in these ten proteins and further evolved into MPXV/USA/2021/MD with mutations in 26 (including mutations in 10 proteins of the MPXV-UK-P2) proteins. It is noteworthy that specific amino acid mutations in these 25/26 (presence in MPXV/USA/2021/MD) proteins are present in B.1 viruses. Overall, from 2017 to 2022, MPXV's mutation and spread suggest that this virus continues to evolve through amino acid point mutation in the proteins.